Efektivitas Metode Edukasi Partisipatif (Simulasi Dan Role Play) dalam Penguatan Literasi Kesehatan Reproduksi Keluarga pada Calon Pengantin di Kantor Urusan Agama Kota Bandung - Inna Noor Inayati (Lembaga Pengembangan Kinerja Dosen, 2026)
Introduction: Premarital reproductive health readiness is a vital foundation for building quality families (Sakinah). The Ministry of Religious Affairs' Marriage Guidance Program serves as a strategic platform for this intervention. This study aims to analyze the effectiveness of participatory education methods in strengthening Prospective Couples' (Catin) literacy and communication skills regarding reproductive health. Method: The activity was conducted in 10 face-to-face sessions throughout 2022 at 10 Religious Affairs Offices (KUA) across Bandung City, involving ± 300 Catins. This research employed a Pure Qualitative Descriptive design. Data were collected through Participatory Observation and Verbal Feedback to analyze the process, interactions, and success of implementing Discussion, Simulation, and Role Play methods. Results: The Marriage Guidance Program proved to be effective in terms of process and interaction. Observation revealed very high Catin participation levels and the significant success of the role play method in breaking down communication barriers regarding sensitive issues. The key finding was the improvement in Catin's practical communication skills, particularly in training husbands' empathetic attitudes toward wives' special conditions and wives' ability to dialogue their health needs, in accordance with religious and health ethics. Conclusion: Participatory education methods are highly effective in transferring psychosocial and communication skills, making The Marriage Guidance Program a sustainable upstream health promotion strategy that deserves reinforcement and institutionalization.